A Review of Automatic Casting Defect Recognition Methods Based on Deep Learning - Wang, Shiyun; Bi, Xinhuan (International Journal of Mechanical and Electrical Engineering, 2025)
Casting defect detection is a crucial link in industrial production, directly affecting product quality and safety. Traditional manual inspection methods, due to their low efficiency, strong subjectivity, and high missed detection rates, can no longer meet the demands of modern intelligent manufacturing. In recent years, the breakthrough progress of deep learning technology in the field of image recognition has provided new solutions for automated casting defect detection. This paper systematically reviews automatic casting defect recognition methods based on deep learning, focusing on aspects such as algorithm improvements, practical applications, and future development directions. It discusses in detail the optimization strategies of object detection algorithms (such as the YOLO series, Mask R-CNN) and semantic segmentation algorithms (such as U-Net, Retina Net), and summarizes the latest achievements in industrial inspection system development. Finally, it prospects future research directions including self-supervised learning, unsupervised learning, and real-time quantitative analysis, aiming to promote the development of casting inspection technology towards intelligence and automation.